How does the COVID-19 cause seizure and epilepsy in patients? The potential mechanisms - Nikbakht, Farnaz; Mohammadkhanizadeh, Ali; Mohammadi, Ekram (Multiple sclerosis and related disorders, 2020)
•Seizure is one symptom of COVID-19.•Cytokine-storm in the brain is the most important reason of seizure in COVID-19•Pro-inflammatory cytokines cause neuronal hyper-excitation. The new coronavirus has spread throughout the world in a very short time and now has become a pandemic. Most infected people have symptoms such as dry cough, dyspnea, tiredness, and fever. However, the Covid-19 infection disrupts various organs, including the liver, kidney, and nervous system. Common neurological symptoms of the Covid-19 infection include delirium, confusion, headache, and loss of sense of smell and taste. In rare cases it can cause stroke and epilepsy. The virus enters the nervous system either directly through nerve pathways or indirectly through the ACE2 receptor. The neurological symptoms of a Covid-19 infection in the brain are mainly due to either the entry of pro-inflammatory cytokines into the nervous system or the production of these cytokines by microglia and astrocytes. Pro-inflammatory cytokines can cause blood-brain barrier disruption, increase in glutamate and aspartate and reduce GABA levels, impairs the function of ion channels, and finally, high levels of cytokines can cause epilepsy. Understanding the potential mechanisms is necessary to gain better insight into COVID-19 induced seizure pathogenesis and to design the correct treatment strategies to achieve appropriate treatment for seizure and epilepsy.